Balanced pulse generator for ultra‐wideband radar application. Issue 4 (1st February 2013) - Xia, Xinfan; Liu, Lihua; Guan, Hongfei; Fang, Guangyou
Abstract : A balanced pulse generator with high voltage amplitude and pulse width in the picoseconds region is described. It can operate well at the pulse repetition frequency (PRF) up to 500 kHz. The proposed generator contains four NPN silicon power transistors operating in avalanche mode and a pair of pulse shaping circuits which effectively utilise the transition characteristics of a step recovery diode. Measurement results are presented, which show the output of the generator are balanced pulses with peak values of ±46 V at 100 kHz PRF and approximately 330 ps full‐width at half‐maximum in width.